Case report: A rare case of a long-term survivor of glioblastoma who underwent two courses of hypofractionated radiotherapy as part of her care - Midhad Mrvoljak; Midhad Mrvoljak; Shubhendu Mishra; Liam Chen; Liam Chen; Elizabeth Neil; Elizabeth Neil; Eric Ehler; Stephanie Terezakis; Stephanie Terezakis; Lindsey Sloan; Lindsey Sloan (Frontiers in Oncology)
Glioblastoma (GB) is a primary brain tumor that is lethal and challenging to treat. The 3-year overall survival (OS) of patients with this diagnosis has stayed the same since 2005. The patient is a 75-year-old woman who presented with progressive aphasia and was diagnosed with GB (WHO grade 4, IDH1/IDH2 wild type, ATRX intact, p53 and PTEN mutant, BRAF non-mutated, O6-methylguanine-DNA methyltransferase promoter methylated) and who underwent surgical resection, hypofractionated radiotherapy (HFRT) using intensity-modulated radiotherapy (IMRT) (4,005 cGy in 15 fractions) alone, and adjuvant temozolomide (TMZ). She was progression-free for approximately 20 months. Although planned, concurrent TMZ was not used during the complete first course of HFRT due to the patient’s performance status. After recurrence, another HFRT (35 Gy in 10 fractions) was employed. She was progression-free on imaging for 8 months until a recent follow-up scan showed potential progression versus radiation-related change. At the time of this case report, her care is still ongoing. This represents a rare case of a long-term survivor of GB who has received two courses of HFRT, a treatment option that is usually used in those with predicted shorter survival times.